Figure of Vamanavatara Vishnu - Temples of India Project Team (Jio Institute, 2024)
Vamanavatara Vishnu, a detailed view of the presiding deity in the garbhagriha (sanctum sanctorum) of the Vamana Temple (Temple 4), Baroli group of temples.